Chimerism as the basis for organ repair. Issue 1 (29th September 2020) - Vadakke‐Madathil, Sangeetha; Chaudhry, Hina W.
Abstract: Organ and tissue repair are complex processes involving signaling molecules, growth factors, and cell cycle regulators that act in concert to promote cell division and differentiation at sites of injury. In embryonic development, progenitor fetal cells are actively involved in reparative mechanisms and display a biphasic interaction with the mother; and there is constant trafficking of fetal cells into maternal circulation and vice versa. This phenomenon of fetal microchimerism may have significant impact considering the primitive, multilineage nature of these cells. In published work, we have reported that fetal‐derived placental cells expressing the homeodomain protein CDX2 retain all "stem" functional proteins of embryonic stem cells yet are endowed with additional functions in areas of growth, survival, homing, and immune modulation. These cells exhibit multipotency in vitro and in vivo, giving rise to spontaneously beating cardiomyocytes and vascular cells. In mouse models, CDX2 cells from female placentas can be administered intravenously to male mice subjected to myocardial infarction with subsequent homing of the CDX2 cells to infarcted areas and evidence of cellular regeneration with enhanced cardiac function. Elucidating the role of microchimeric fetal‐derived placental cells may have broader scientific potential, as one can envision allogeneic cell therapy strategies targeted at tissue regeneration for a variety of organ systems. Abstract : There is constant trafficking of fetal cells into maternal circulation and vice versa. This phenomenon, of fetal microchimerism, may have significant impact considering the primitive, multilineage nature of fetal cells. Elucidating the role of microchimeric fetal‐derived placental cells may have broader scientific potential, as one can envision allogeneic cell therapy strategies targeted at tissue regeneration for a variety of organ systems.